MORPHOLOGICAL VARIABILITY CHARACTERISTICS OF FEMALE GAMBUSIA HOLBROOKI (TELEOSTEI: POECILIIDAE) IN NATURAL AND ARTIFICIAL WATER BODIES OF THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2025)
Holbrook gambusia - Gambusia holbrooki (Girard, 1859) was introduced to the water bodies of Central Asia for the purpose of combating malaria mosquitoes and is found in almost all large and small water bodies in the territory of Uzbekistan. This article analyzes and compares the morphological parameters of Holbrook gambusia found in the Big Fergana Canal and the Qoradaryo water basins. Studying the morphological variability of fish in different water bodies is important not only for the correct identification of species, but also for understanding the process of differentiation within the species.The analysis showed that Gambusia holbrooki distributed in artificial and natural water bodies of the Fergana Valley differed in 3 morphometric traits (body depth, head depth from the nape, and snout length). The variability (V) of the two populations was also evaluated based on the coefficient of variation. According to this, it was found that the samples of Holbrook gambusia from the Big Fergana Canal had high variability in 2 traits, medium variability in 8 traits, and low variability in 12 traits. In the samples from the Qoradaryo, high variability was observed in 6 traits, medium variability in 10 traits, and low variability in 7 traits.